Efektivitas Penggunaan Media Leaflet Pencegahan Secondhand Vape Smoker Terhadap Risiko Secondhand Vape Smoker di UMKT - silvia Faronika Alimasita; Nida Amalia (Borneo Student Research (BSR), 2021)
Purpose of study: To determine the effectiveness of Leaflet Media usage to risk prevention for Secondhand Vape Smoker at Muhammadiyah University in East Kalimantan. Methodlology: This research is a quantitative study that using the Pre-Experiment research method, the design used is One Group Pretest Posttest, the sample is taken with a total of 30 subject respondent of Public Health Study Program Specialization in Health Promotion students at Muhammadiyah University in East Kalimantan. Results: The results of the study the following data were obtained: average pre-test media (7.79) and post-test (10.14). Wilcoxon Sign Test results with a P-value of 0.000 <0.05 which shows the effectiveness of the leaflet media to prevent the risk of secondhand vape smoker. Average knowledge pre-test (6.76) and post-test (1.00). Wilcoxon Sign Test results with a P-value of 0.000 <0.05 which indicate an increase in knowledge of the risk prevention of secondhand vape smoker before and after treatment. The average pre-test attitude (1.21) and post-test (8.03) with the Wilcoxon Sign Test 0.000 <0.05 which means an increase in attitude towards the risk prevention of secondhand vape smoker. Average pre-test (1.00) and post-test (0.062) with the results of the Wilcoxon Sign Test 0.001 <0.05, which means an increase in action against the risk of secondhand vape smoker prevention. Applications: For the community, students, and researchers are expected to upgrade knowledge about the hazards and Secondhand Vape Smoker risk prevention.